2016
DOI: 10.1111/asj.12601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of apple pomace‐mixed silage on growth performance and meat quality in finishing pigs

Abstract: We measured the growth performance and meat quality of 10 crossbred (Yorkshire × Duroc × Landrace) neutered male pigs to evaluate the effects of apple pomace-mixed silage (APMS). The pigs were divided into two groups and were respectively fed the control feed and the AMPS ad libitum during the experiment. No difference was found in the finished body weight, average daily gain, carcass weight, back fat thickness or dressing ratio between the control and the AMPS treatments, but average dairy feed intake (dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…However, fermented feed has been shown to improve meat quality of finishing pigs. Study by Fang et al reported that feeding fermented apple pomace to finishing pigs reduced the drip loss [31]. Additionally, a study by Kim et al reported dietary supplementation of fermented persimmon shell improved sensory tenderness in pork longissimus muscle [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, fermented feed has been shown to improve meat quality of finishing pigs. Study by Fang et al reported that feeding fermented apple pomace to finishing pigs reduced the drip loss [31]. Additionally, a study by Kim et al reported dietary supplementation of fermented persimmon shell improved sensory tenderness in pork longissimus muscle [18].…”
Section: Discussionmentioning
confidence: 99%
“…No effect in feed intake between control and experimental diets were indicated in these studies. A related experiment with pigs fed with silage containing apple pomace indicated minimal or non-significant effects in the growth performance, except for a reduction in daily feed intake and an increase in feed efficiency in animals fed with apple pomace silage [35]. Additionally, this study also indicated a significant increase in the content of some individual polyunsaturated fatty acids in back fat, whereas the content of few saturated and monounsaturated fatty acids in back fat were reduced.…”
Section: Utilization In Silage or As A Feed Supplement For Animal Pro...mentioning
confidence: 48%
“…It is worth mentioning that the modification of foods obtained from animals fed with fermented pomace fits in the strategy to naturally enrich foods with nutrients and functional compounds [43]. This strategy is supported by studies with apple [35], grape [38,39], olive and tomato pomaces [40,41]. However, additional studies are still necessary to identify relevant sources due to the controversial results such as those reported for pomegranate pomace in chicken meat [42].…”
Section: Utilization In Silage or As A Feed Supplement For Animal Pro...mentioning
confidence: 98%
“…Grazing affected the fatty acid composition with increasing palmitic acid and decreasing steric acid in LTL. It is reported that apple pomace-mixed silage can increase palmitic acid and decrease steric acid in backfat, which can be related to dietary fiber [ 31 ]. More importantly, the researches on functional pork related to fatty acid composition mainly focus on the n-6/n-3 PUFA ratio, and n-3 PUFA and n-6PUFA are closely related to the occurrence and development of human diseases.…”
Section: Discussionmentioning
confidence: 99%